Assessment of endoscopic Doppler to guide hemostasis in high risk peptic ulcer bleeding. (2nd November 2018) - Kantowski, Marcus; Schoepfer, Alain M.; Settmacher, Utz; Stallmach, Andreas; Schmidt, Carsten
Abstract: Introduction: Rebleeding or emergency surgery in failed endoscopic therapy of peptic ulcer bleeding are associated with high rates of morbidity and mortality. The clinical benefit of an endoscopic Doppler (ED) examination prior to endoscopic injection therapy was evaluated in high risk ulcer patients for rebleeding episode. Standard injection therapy (non-Doppler (ND)) was compared with targeted injection therapy after examination of the supplying vessel in the ulcer base by the ED. Materials and methods: Sixty patients with peptic ulcer bleeding (Forrest Ia–IIa; Rockall score of 5 or higher) were included in the study. Patients were assigned to ED or ND group with conventional therapy by chance. In the ND group injection was directed by the visual aspect of the ulcer, whereas in ED therapy was directed by ED. Results: Thirty-five patients were allocated to the ED group, and 25 to the ND group, respectively. No significant differences in patient or ulcer characteristics were observed regarding ulcer size, localization, Forrest classification or endoscopic treatment. Recurrent bleeding was observed in 7/35 (20%) in the ED group and in 13/25 (52%) of patients in the ND group ( p = .013). Fewer ED patients needed surgery for rebleeding (1/35 vs. 6/25; p = .017). Bleeding related, but not all-cause mortality was significantly lower in the ED group (1/35 vs. 6/25, p = .017). Discussion: In this comparative analysis, use of ED to guide hemostatic therapy was associated with a significant reduction in recurrence of bleeding, surgical intervention and bleeding associated mortality.